Local Government Authority in The Field of Religion; A Study of Regional Regulation (Perda) on Zakat in Riau Province - Suparto Suparto; Admiral Admiral; Deni Jaya Saputra (Fakultas Syariah, 2022)
Zakat as one of the five pillars of Islam is the obligation of every Muslim who can afford it and is reserved for those who have the right to receive it. With a proper management, zakat is a potential resource that can be utilized for the progress and prosperity of society. In 2018, The Government of Riau Province established a Regional Regulation (Perda) on zakat but did not obtain a Register Number from the Minister of Home Affairs so that the Regional Regulations could not be enacted in regional papers. The purpose of this study was to determine the authority of the local government in making a Regional Regulation on zakat and the urgency of zakat management to be regulated by a Regional Regulation. This research is a normative juridical with a statutory approach. The data used is secondary data and analyzed qualitatively descriptive. Based on the discussion, it was found that the authority of the Regional Government in the field of Religion; namely Zakat, is only limited to proposing the formation of the National Amil Zakat Agency (BAZNAS) to the Minister, while the regulation of Zakat through Regional Regulations violates statutory regulations considering that the mandate of the formation of Regional Regulations is only related to the implementation of regional autonomy in the context of concurrent affairs. On the other hand, the management of zakat which is regulated by Perda as in Bengkalis Regency managed to make the receipt of zakat has increased compared to before the existence of Perda. The government is not consistent in conducting executive previews of the Regional Regulation (Perda) on Zakat, because the Province of West Nusa Tenggara (NTB) has a Perda on Zakat, that is No. 9 of 2015 as well as Bengkalis Regency has a Perda on Zakat, No. 3 of 2018 and received a Register Number from the Governor as a Representative of the Central Government. In the future, the Government must be consistent and equitable in conducting executive previews of the Regional Regulation on Zakat so that there are no disparities between regions in Indonesia.